Analyses of moral values of student activists’ protest demonstrations in Sunan Kalijaga State Islamic University Yogyakarta - Maksudin Maksudin (Jurnal Cakrawala Pendidikan, 2023)
Protest demonstrations are legal by Laws of the Republic of Indonesia Number 9 Year 1998 about Freedom to Convey Opinions in front of the Public. This study aims to comprehensively analyze the moral values of the student activists’ protest demonstrations in Sunan Kalijaga State Islamic University Yogyakarta regarding the causes, demands, and processions. The study was done using the principles of field research, the qualitative approach, by the case-study method. The researcher holistically looked into the activities and processes of the students’ protest demonstrations. Data were elicited by the techniques of in-depth interviews, questionnaires, observations, and documentation. Data were analyzed by using the NVivo 12 Plus software. Findings show that student activists’ protest demonstrations generally focus on the single university fee policy and other campus and Government policies that are not pro-students and citizens. Students’ protest demonstrations in Sunan Kalijaga State Islamic University (SIU) Yogyakarta carry along 28 good moral values and 15 bad moral values. It is shown that students’ demonstrations have more good moral values than bad, with a difference of 13 moral values. It can be concluded that it is not appropriate to verdict students’ protest demonstrations to all inflict neither bad nor all good moral values.